2022
DOI: 10.1002/jcla.24204
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated circulating microRNA‐126 in chronic obstructive pulmonary disease: linkage with acute exacerbation risk, severity degree, and inflammatory cytokines

Abstract: Background: is engaged in respiratory diseases via regulating airway tissue injury and pulmonary inflammation, while its relation with chronic obstructive pulmonary disease (COPD) is not reported. The study aimed to evaluate the value of miR-126 for estimating COPD acute exacerbation risk and its relation to disease severity and inflammatory cytokines in COPD patients. Methods: This study was a case-control study. Seventy acute exacerbation COPD (AECOPD) patients, 70 stable COPD (SCOPD) patients, and 70 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Of the 12 di erentially expressed miRNAs, miR-28-3p was most signi cantly down-regulated and miR-212-5p was most signi cantly up-regulated [53]. More recently, a study showed that two constructed miRNA-mRNA pathways; miR-126-5p and miR-130-5p-FOXO1 could be potential biomarkers for the diagnosis and treatment of COPD 54 . This year, a study showed that miR-126 was higher in COPD patients with acute exacerbation compared to stable COPD patients and healthy non-COPD patients and distinguished the groups.…”
Section: Mirnamentioning
confidence: 99%
“…Of the 12 di erentially expressed miRNAs, miR-28-3p was most signi cantly down-regulated and miR-212-5p was most signi cantly up-regulated [53]. More recently, a study showed that two constructed miRNA-mRNA pathways; miR-126-5p and miR-130-5p-FOXO1 could be potential biomarkers for the diagnosis and treatment of COPD 54 . This year, a study showed that miR-126 was higher in COPD patients with acute exacerbation compared to stable COPD patients and healthy non-COPD patients and distinguished the groups.…”
Section: Mirnamentioning
confidence: 99%
“… 11 Wang et al’s case-control study highlighted the significance of plasma miR-126 expression in COPD, revealing its potential as a distinguishing biomarker not only between COPD patients and healthy controls but also between AECOPD and stable COPD (SCOPD) patients. 12 With the continual advancement of sequencing technology, the growing body of research on miRNA for COPD diagnosis prompted our meta-analysis to systematically integrate and analyze findings from multiple independent studies, aiming to derive more comprehensive and reliable conclusions regarding the utility of miRNA in COPD diagnosis.…”
Section: Introductionmentioning
confidence: 99%